Penerapan Aplikasi Kurikulum “PG” Terhadap Perancangan Interior See Me Grow Day Care - Jessica Soetrisno (Intra, 2013)
Day care is a place that makes "second home" for children who have parents who have a lot of activity. Has a variety of activities, so as to meet the metabolic activity and motor learning them. The method used was a qualitative method. Within a day care there is the curriculum. The curriculum is used as a basis for making a decision mentukan learning system, and the necessary space requirements. Also needs a room is determined by the activity there. Activity a Day Care will be one of the main factors for the development and the smooth development of the child. This study aims to determine the application of the curriculum to the design of the interior. Factors that support the activities can be done through the standardization is achieved through the size of the furniture, classroom arrangement, materials, lighting, and ventilation are used. Curriculum role in the process of learning, and support the necessary conditions for an interior children in a Day Care for children dapatberkembang optimally. The results are contained in a Day Care, has several major requirements that is comfortable, healthy, and safe. And according to the needs of the activity required.